Risk Factors for Acquisition of Endemic Blastomycosis. Issue 4 (2009) - Choptiany, Maxym; Wiebe, Lyle; Limerick, Bill; Sarsfield, Pete; Cheang, Mary; Light, Bruce; Hammond, Greg; MacDonald, Kerry; Trepman, Elly; Pappas, Peter; Embil, John M
Abstract : BACKGROUND: Blastomycosis is potentially fatal, but environmental risk factors for acquiring blastomycosis are not well established. METHOD: Matched cross-sectional questionnaire of 112 patients with history of blastomycosis and 118 control subjects in Manitoba and northwestern Ontario. RESULTS: The most common tissues involved with blastomycosis were pulmonary, skin and soft tissues, and bone. A significantly greater proportion of patients with blastomycosis than control subjects were involved in outdoor occupations. A significantly greater percentage of patients with blastomycosis were immunosuppressed either from collagen vascular disease or immunosuppressive therapy, or had hypothyroidism. A significant association between canine and human blastomycosis was not observed. CONCLUSIONS: Independent risk factors for development of blastomycosis included immunosuppression for any reason (including drugs or disease), collagen vascular disease, being an outdoor worker, and having a coworker with blastomycosis. Canine blastomycosis was not a risk factor for human disease in dog owners.